Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let us say we have the following ODE: $$x^7\frac{d^4y}{dx^4} - y' = 0$$

To classify the singular point at $\infty$, we need of course to make a substitution: $x = \frac{1}{t}$, and then evaluate the point $t = 0$. My question is: how can we transform this differential equations in terms on $x$ and $t$? It seems like a very elaborate computational task. Is there an easy way to do this???

share|improve this question

1 Answer 1

up vote 1 down vote accepted

I think there is no other way around it but to use the chain rule: \begin{align} \frac{d y}{d x} &= \frac{d y}{d t}\frac{d t}{d x} = -\frac{1}{x^2} \frac{d y}{d t} = -t^2 \frac{d y}{d t}\\ \frac{d^2 y}{d x^2} &= \frac{d}{d t} \left(\frac{d y}{d x}\right) \frac{d t}{d x} = -t^2 \frac{d}{d t}\left(-t^2 \frac{d y}{d t}\right) =2 t^3 \frac{d y}{dt} + t^4 \frac{d^2 y}{d t^2}\\ \frac{d^3 y}{d x^3} &= -t^2 \frac{d}{d t}\left(2 t^3 \frac{d y}{dt} + t^4 \frac{d^2 y}{d t^2}\right) = -6 t^4 \frac{d y}{d t} -6 t^5 \frac{d^2 y}{d t^2} - t^3 \frac{d^3 y}{d t^3}\\ \frac{d^4 y}{d x^4} &= -t^2 \frac{d}{dt} \left(-6 t^4 \frac{d y}{d t} -6 t^5 \frac{d^2 y}{d t^2} - t^3 \frac{d^3 y}{d t^3}\right)\\ &= 24t^5 \frac{d y}{d t} + 36 t^6 \frac{d^2 y}{d t^2} + 12 t^7 \frac{d^3 y}{d t^3} + t^8 \frac{d^4 y}{d t^4} \end{align}

I didn't doublecheck my calculations, and I can't vouch I didn't made a mistake. The conceptual work is correct though. You should do the math yourself.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.